Development of a robotically-based automated biodosimetry tool for high-throughput radiological triage. (7th May 2010) - Chen, Youhua; Zhang, Jian; Wang, Hongliang; Simaan, Nabil; Yao, Y.; Garty, Guy; Xu, Yanping; Lyulko, Oleksandra; Turner, Helen; Randers-Pehrson, Gerhard; Brenner, D.J.
To provide the best opportunities for life-saving interventions in the event of a radiological or nuclear threat, there is an urgent need to improve the speed and efficiency of biodosimetric assays for triage and therapy. A rapid automated biodosimetric system used to assess thousands of individual radiation exposure doses is helpful to curb mass panic, and to conserve limited medical resources. This paper presents the development of a new robotically-based automated biodosimetry tool (RABiT). The RABiT is capable of automating two mature biodosimetry assays: the micronucleus and γ-H2AX assay. The design considerations guiding the hardware and software architecture are presented with focus on ease of implementation, methods of communication and need for real-time control versus soft time control cycles. Advanced technological developments for the RABiT including multipurpose gripper, non-contact laser cutting, automated biology protocols and transferring of the samples to a transparent substrate and high-speed multiple camera imaging are described in detail. The evaluation results show that the RABiT prototype has a throughput of 5, 859 samples in an 18-hour duty cycle.